Using graph algorithm and classification technique for finding an optimal bus route in time-dependent travel times - Deelertmongkolchai, Satjayod; Chumwatana, Todsanai; Thaiupathump, Choonhapong (2016)
In the last decade, traffic jam has been regarded as a main problems for Bangkok.Most people selects a bus option for traveling because it is cheap and cover every area in Bangkok. However, they are suffering from the long hours in traffic jam especially in rush hour.They also cannot avoid this such jam as bus routes are fixed by Bangkok Mass Transit Authority (BMTA).This paper aims to propose a technique for finding an Optimal Bus Route in Time-Dependent Travel Times by using graph algorithm and data mining technique. The proposed technique is able to find a least spent travel time path between two nodes in a bus network with time-dependence.Graph algorithm is used to generate all possible paths to reveal the distances.Classification technique is then used to analysis traffic situation in different period of the time.By analysis traffic situation, date, time, week, month, location are used as a main factor for training process in classification technique.From the experimental studies, the proposed technique is able to show the best route from any given node to the final destination depending on the different period of the time.The proposed technique provides significant benefit for traveler to select the best bus route, which is short distance and fast, among generated routes